2014
DOI: 10.1136/bmj.g5493
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment failure in four common infections in UK primary care 1991-2012: longitudinal analysis

Abstract: Objective To characterise failure of antibiotic treatment in primary care in the United Kingdom in four common infection classes from 1991 to 2012.Design Longitudinal analysis of failure rates for first line antibiotic monotherapies associated with diagnoses for upper and lower respiratory tract infections, skin and soft tissue infections, and acute otitis media. Setting Routine primary care data from the UK Clinical Practice Research Datalink (CPRD).Main outcome measures Adjusted rates of treatment failure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 13 publications
4
78
0
3
Order By: Relevance
“…Antimicrobial resistance poses a substantial threat to public health as it is related to treatment failure, prolonged hospitalisation, increased cost of care and increased mortality [1][2][3][4]. Both ecological studies and randomised controlled trials in individual patients have demonstrated a link between antibiotic use and resistance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance poses a substantial threat to public health as it is related to treatment failure, prolonged hospitalisation, increased cost of care and increased mortality [1][2][3][4]. Both ecological studies and randomised controlled trials in individual patients have demonstrated a link between antibiotic use and resistance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Yet 6.2% of our population even received two antibiotic courses for LRTI within two weeks. Treatment failure rates of 20% have been described previously but these included prescriptions for pneumonia and further antibiotics for all indications [9]. We present more specific data for LRTI, which can assist to plan future work.…”
Section: Discussionmentioning
confidence: 95%
“…Amoxicillin treats Streptococcus pneumoniae , the most common bacterial cause of LRTI, hence our finding of fewer repeat prescriptions after initial amoxicillin therapy could be clinically plausible [12]. Whilst the effect sizes were small, LRTI are very common [9]. Hence even small differences of less than 1% could theoretically result in meaningful differences in antibiotic prescriptions due to the size of the population, if they were true.…”
Section: Discussionmentioning
confidence: 99%
“…Este antibiótico, como muchos otros, puede presentar un aumento de su consumo en ciertos períodos del año, tal como los meses de invierno [17], aumentando sus probabilidades de uso inadecuado. A pesar de ser el antibiótico de mayor prescripción en otitis, infecciones del tracto respiratorio, de la piel y de los tejidos blandos, Currie y colaboradores [11] mostraron que la amoxicilina era la de menor tasa de fracaso del tratamiento.…”
Section: Variablesunclassified
“…Esta se emplea en diagnósticos como la otitis [10,11], sinusitis [10], amigdalitis [10], infecciones del tracto respiratorio [11], infecciones de la piel y tejidos blandos [11], entre otros. Según varios estudios, la amoxicilina y las penicilinas de amplio espectro son el antibiótico y el subgrupo farmacológico más consumido a nivel comunitario, en Colombia [7,[12][13][14], en América Latina [15] y en distintos países del mundo [16][17][18][19][20][21][22].…”
Section: Introductionunclassified